A recent improvement in the Navy's numerical-statistical scheme for forecasting the motion of hurricanes and typhoons - Daley, M. J.; Rinard, Stephen K.; Renard, Robert Joseph (Monterey, California. Naval Postgraduate School, 1970)
The Navy's numerical-statistical scheme for forecasting the motion of tropical cyclones is reviewed. The numerical component (HATRACK) represents geostrophic steering of the cyclone by the Fleet Numerical Weather Central's smoothed isobaric height fields at 1000, 700, and 500 mb. The statistical component refers to the correction for bias in the numerical steering. The paper introduces an improvement in application of the statistical correction for bias. The enhanced scheme, MODIFIED HATRACK, is applied to forecasts of all named North Atlantic tropical cyclones in 1967 and 1968 and to a select number of 1967 North Pacific tropical storms and typhoons. The accuracy of MODIFIED HATRACK is found to excel the official forecast and that of the National Hurricane Center's NHC-67 technique for all forecast intervals through 48 hours. MODIFIED HATRACK errors range from an average of 40 nautical miles at 12 hours to 240 nautical miles at 48 hours. Such figures represent a 60 percent and a 10 percent reduction in errors, respectively, compared to official forecasts in the Atlantic. For the Pacific, the error reductions are of the order of 15 percent. (Author) http://archive.org/details/recentimprovemen00rena